In vitro intestinal digestion of lipids from the marine diatom Porosira glacialis compared to commercial LC n-3 PUFA products - Dalheim, Lars; Svenning, Jon Brage; Olsen, Ragnar Ludvig (PLOS ONE, 2021)
Marine sources of long chain omega-3 polyunsaturated fatty acids (LC n-3 PUFA) are in high demand for use in health supplements. Mass cultivated marine microalgae is a promising and sustainable source of LC n-3 PUFA, which relieves pressure on natural fish stocks. The lipid class profile from cultivated photosynthetic algae differ from the marine organisms currently used for the production of LC n-3 PUFA. The objective of this study was to compare in vitro intestinal digestion of oil extracted from the cold-adapted marine diatom Porosira glacialis with commercially available LC n-3 PUFA supplements; cod liver oil, krill oil, ethyl ester concentrate, and oil from the copepod Calanus finmarchicus (Calanus® oil). The changes in the free fatty acids and neutral and polar lipids during the enzymatic hydrolysis were characterized by liquid and gas chromatography. In Calanus® oil and the Ethyl ester concentrate, the free fatty acids increased very little (4.0 and 4.6%, respectively) during digestion. In comparison, free fatty acids in Krill oil and P. glacialis oil increased by 14.7 and 17.0%, respectively. Cod liver oil had the highest increase (28.2%) in free fatty acids during the digestion. Monounsaturated and saturated fatty acids were more easily released than polyunsaturated fatty acids in all five oils.